On the persistence of p element in cultured lineages of Drosophila melanogaster - Rozhok, A.I.; Ievdokymenko, K.S.; Kozeretska, I.A. (Цитология и генетика, 2012)
P transposon is known to have invaded the Drosophila melanogaster genome in the 1950s as a result of horizontal transmission from D. willistoni. Part of the evidence supporting the timing of its invasion comes from analyses of cultured drosophila lineages originating from wild flies cultivated long time in laboratory before analysis. Such analyses have shown that P element was absent from the genomes of cultured lineages established from wild flies caught from the wild before the 1950s. Although the hypothesis of P element transmission has obtained multiple lines of evidence and is beyond doubt today, we decided to test whether analysis of cultured lineages can provide some temporal information on the P element population dynamics. In the present work we demonstrate that P element present the in wildcaught flies may be lost in the cultured fly lineages after some generations. This result is in accordance with the results of at least one published work and suggests that analysis of the cultured fly lineages may sometimes be unreliable in establishing historical trends in P element population dynamics, as the transposon may be occasionally lost, perhaps in the highly inbred lineages in which not all founding females carry it. Известно, что Р транспозон попал в геном Drosophila melanogaster в 50-х годах прошлого столетия результате горизонтального переноса от D. willistoni. Частично время инвазии было рассчитано на основании анализа культивируемых линий дрозофилы, которые происходят от диких особей, культивируемых как изосамковые линии задолго до анализа. Такой анализ показал, что Р элемент отсутствовал в геномах культивируе-мых линий, которые основаны из особей, собранных в природе до 1950 г. Хотя гипотеза переноса Р элемента подтверждена различными доказательствами и ее достоверность не вызывает сомнений, мы решили проверить, дает ли анализ культивируемых линий информацию о временных факторах популяционной динамики Р элемента. В настоящей работе мы показываем, что Р элемент, присутствующий в диких особях, может быть утрачен в культивируемых линиях через некоторое количество поколений. Такие результаты согласуются с данными как минимум одной опубликованной работы и свидетельствуют о том, что анализ культивируемых линий дрозофилы не всегда надежен при воссоздании исторических трендов популяционной динамики Р элемента, поскольку этот транспозон может быть случайным образом утерян, очевидно, вследствие высокой инбредности линий, у которых геномы не всех самок-основателей содержали его. Відомо, що Р транспозон потрапив до геному Drosophila melanogaster у 50-х роках минулого століття в результаті горизонтального переносу від D. willistoni. Частково час інвазії був розрахований на основі аналізу культивованих ліній дрозофіли, що походять від диких особин, котрі культивувались у лабораторії як ізосамкові лінії задовго до аналізу. Такий аналіз показав, що Р елемент був відсутній у геномах культивованих ліній, заснованих з особин, що зібрані у природі до 1950 р. Хоча гіпотеза переносу Р елемента підтверджується різноманітними доказами та її достовірність не викликає сумніву, ми вирішили перевірити, чи дає аналіз культивованих ліній інформацію щодо часового фактора популяційної динаміки Р елемента. В даній роботі ми показуємо, що Р елемент, присутній у диких особин, може втрачатись в культивованих лініях через певну кількість поколінь. Такі результати узгоджуються з даними щонайменше однієї опублікованої роботи та свідчать про те, що аналіз культивованих ліній дрозофіли може інколи бути ненадійним для відтворення історичних трендів популяційної динаміки Р елемента, оскільки цей транспозон може випадковим чином втрачатись, очевидно, через високу інбредність ліній, в яких геноми не всіх самиць-засновників містили його.